Development Of Professional Competence For Arabic Language Teachers At Madrasah Aliyah Model Hafshawaty Zainul Hasan Genggong - Ainur Rofiq Sofa; Abd Aziz (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
This community service activity emphasizes the importance of preparing proposals and reports on Classroom Action Research (CAR) to improve the quality of Arabic language learning. It is expected that Arabic teachers at Madrasah Aliyah Model Hafshawaty Zainul Hasan Genggong will understand the steps in preparing CAR, enhance the quality of Arabic language learning, and draft relevant CAR proposals. To achieve this goal, training, and education were conducted at Madrasah Aliyah Model Hafshawaty Zainul Hasan Genggong with 25 participants from May 31 to June 4, 2024, over five days. The methods used included lectures, discussions, and hands-on practice. Participants received material through lectures, engaged in group discussions, and prepared CAR proposals with guidance from facilitators. The training results showed that this activity was highly beneficial for Arabic teachers at Madrasah Aliyah Model Hafshawaty Zainul Hasan Genggong. The teachers gained a better understanding of the importance of professional development through CAR and received guidance in preparing proposals and conducting classroom action research. In conclusion, the program significantly enhanced the teachers' ability to conduct effective CAR, contributing to the overall improvement of Arabic language education at the institution.